Cryobiotechnology of tropical seeds - scale, scope and hope - H. W. Pritchard (2018)
© 2017, International Society for Horticultural Science. All rights reserved. Plants provide essential ecosystem services that benefit humankind, yet their existence is subject to an increasing number of threats, including global environmental change. Anticipated impacts on future access to medicines, nutritious foods, particularly indigenous fruits, and sustainable biofuels, demands that action is taken to protect and conserve such valuable, neglected and underutilized species (NUS), especially in the tropics where the use of non-timber forest products (NTFP) is considerable. Primarily, the protection of such plant genetic resources is achieved through the complementary approaches of in situ and ex situ conservation; for the latter, generally as dry seeds stored at -20°C. However, tropical forest species - which are estimated to constitute about 50% of the world’s plants - tend not to be so readily amenable to such an approach, and attention is now focusing increasingly on cryopreservation. This review considers the following issues: how plant cryopreservation studies have evolved over time and the extent of application of cryobiotechnology (scale); the policy current drivers and biodiversity needs that provide a framework for current and future plant cryopreservation studies (scope); and which technological innovations, knowledge and understanding might fast-track the science and accelerate the mainstreaming of plant cryopreservation particularly for tropical seeds (hope). Whilst significant progress in plant/seed cryobiotechnology has been made in the last decades, a co-ordinated global research and training programme aimed at accelerating the cryobanking of tropical plants of value to humankind is now urgently needed.